Ties that bind and blind : scorecard of Singapore’s multicultural bonds - Chin, Yolanda (2012)
Given recent events involving race and religion in Singapore between 2007 and 2011, it may be tempting to wonder if Singapore’s multicultural harmony has possibly been strained. A study by the Centre of Excellence for National Security at RSIS argues this is not the case.